Comparison of Initial Experiences of Robot-Assisted Radical Cystectomy with those of Laparoscopic for Bladder Cancer. Issue 4 (July 2014) - Teishima, Jun; Hieda, Keisuke; Inoue, Shogo; Goto, Keisuke; Ikeda, Kenichiro; Ohara, Shinya; Kobayashi, Kanao; Kajiwara, Mitsuru; Matsubara, Akio
Objective: The aim of the present study was to evaluate perioperative outcomes in initial experiences of robot-assisted laparoscopic radical cystectomy (RARC) in comparison with those of laparoscopic radical cystectomy (LRC) for muscle-invasive or high-risk non-muscle-invasive bladder cancer. Methods: We performed RARC on six patients with muscle-invasive or high-risk non-muscle-invasive bladder cancer starting in October 2011. During the same period, another five patients underwent LRC. Perioperative outcomes in initial experiences of RARC were elucidated by comparing them with those of LRC. Results: Robot-assisted procedures were completed in all cases without conversion to open surgery. The median time of pneumoperitoneum was 252 minutes, and the median blood loss was 340 mL. No severe complications were observed. Perioperative outcomes did not significantly differ between RARC and LRC. Although two cases of troubles in uretero-conduit anastomosis sites were observed after LRC, no patients experienced postoperative complication related to urinary diversion after RARC. Conclusions: Our data indicate that RARC is an acceptable option even in the initial period, and it may become one of the most favorable procedures for treatment of muscle-invasive bladder cancer in the near future, although more tests and longer follow-ups are required to confirm its effectiveness and safety.